Incidence study of surgical site infections in a large University Hospital in Rome, first results. (13th November 2019) - Vallone, D; Di Pumpo, M; Gentili, A; Tamburrano, A; Berloco, F; Corbo, M I; Cambieri, A; Damiani, G; Ricciardi, W; Laurenti, P
Abstract: Background: Surgical Site Infections (SSI) represent about a quarter of healthcare associated infections (HAI), increase the risk of mortality and hospital stay and extend healthcare costs. The aim of this work is to evaluate the incidence of SSI in patients undergoing surgical procedures of Hospital Units in the Fondazione Policlinico A. Gemelli IRCCS (FPG). Methods: This descriptive observational monocentric study has a 30-months duration: the first phase was conducted between July 2018 and March 2019. Patients undergoing abdominal surgery procedures were enrolled. Active infection surveillance was performed, according to the ECDC, during the hospital stay and the surgical outpatient visits. We also performed a post-discharge surveillance (PDS) at 30 days (or 90 days if an implant has been inserted), through a telephone interview, made by a medical doctor resident in Public Health. Results: During the first phase were enrolled 431 procedures in 2 Hospital Units, about emergency and hepatobiliary surgery. There were 53 cases of surgical site infection (SSI) highlighted in these procedures. Therefore, SSI's were reported in 12.09% of the procedures. In particular, in 6.28% of cases, SSIs were diagnosed during the hospital stay. The results of this study showed statistically significant differences (p < 0.005) in incidence rate of emergency (10, 70%) and hepatobiliary tract (13, 17%) procedures. The average hospital stay was significant higher (p < 0.001) in patients who developed an SSI (17.27 days) than in patients without SSI (4.89 days). Conclusions: These preliminary results show that the incidence rate of SSI for gastrointestinal procedures is similar to other European Countries (9.6%). The Hospital Health Management of FPG take care to the surveillance of hospital infections and monitor the correct application of the procedures, in line with the standards defined by Joint Commission International for guarantee high level in patients' care. Key messages: Performing a survey to measure the incidence of surgical site infections for surgery procedures is very important to define it and to improve surveillance systems of hospital infections in FPG. Active surveillance of surgical site infections may allow to enhance appropriate preventive measures.